2021
DOI: 10.1021/acs.cgd.1c00652
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Metal (Li, Na, and K) Orthocarbonates: Stabilization of sp3-Bonded Carbon at Pressures above 20 GPa

Abstract: In the present work, based on the density functional theory and crystal structure prediction algorithms, we found novel structures of alkali metal orthocarbonates Li4CO4-C2/c, Na4CO4-C2/c, and K4CO4-P21/c. The pressure of thermodynamic stabilization of the obtained orthocarbonates with respect to decomposition into the corresponding carbonate and oxide ranges from 21 GPa (for K4CO4) to 25 GPa (for Li4CO4). All obtained structures contain isolated groups of [CO4]­tetrahedra. The structures of lithium and sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
(126 reference statements)
2
11
0
Order By: Relevance
“…Theoretical studies have predicted the formation of sp 3 carbonates at pressures and temperatures much lower than are required for the transformation of conventional carbonates for either oxide- or CO 2 -enriched compounds: i.e., for carbonates which have an oxide:CO 2 ratio other than 1:1. Some of these predictions have recently been confirmed by the synthesis of the sp 3 carbonates Ca 2 CO 4 - Pnma , Mg 2 CO 4 - P 2 1 / c , Sr 2 CO 4 - Pnma , , and Sr 3 (CO 4 )­O- I 4/ mcm , which can be obtained at p ≈ 20 GPa and where Sr 2 CO 4 - Pnma and Sr 3 (CO 4 )­O- Pnma can be recovered under ambient conditions. These syntheses have all been conducted by reacting mixtures of an alkaline-earth oxide with the corresponding carbonate: e.g., by reacting CaO with CaCO 3 .…”
Section: Introductionmentioning
confidence: 98%
“…Theoretical studies have predicted the formation of sp 3 carbonates at pressures and temperatures much lower than are required for the transformation of conventional carbonates for either oxide- or CO 2 -enriched compounds: i.e., for carbonates which have an oxide:CO 2 ratio other than 1:1. Some of these predictions have recently been confirmed by the synthesis of the sp 3 carbonates Ca 2 CO 4 - Pnma , Mg 2 CO 4 - P 2 1 / c , Sr 2 CO 4 - Pnma , , and Sr 3 (CO 4 )­O- I 4/ mcm , which can be obtained at p ≈ 20 GPa and where Sr 2 CO 4 - Pnma and Sr 3 (CO 4 )­O- Pnma can be recovered under ambient conditions. These syntheses have all been conducted by reacting mixtures of an alkaline-earth oxide with the corresponding carbonate: e.g., by reacting CaO with CaCO 3 .…”
Section: Introductionmentioning
confidence: 98%
“…A number of new types of carbonates, namely orthocarbonates, in the structure of which carbon atoms are in the sp 3 hybridized state, have been discovered using ab initio crystal structure predictions. [1][2][3][4][5] To date, it has been demonstrated that orthocarbonates of alkaline earth metals could be formed by the reaction of carbonates with the oxides of the corresponding metals. Depending on the ratio of initial reagents, two different phases M 2 CO 4 -Pnma (MCO 3 ÁMO) and M 3 CO 5 -I4/mcm (MCO 3 Á 2MO), where M = Ca, Sr, and Ba, were predicted to be stable beginning from a pressure of 5-20 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…[9] In addition to the described systems with alkaline earth elements, systems with alkaline elements have been also investigated and stability of 2 : 1 structures above 20 GPa have been shown. [10,11] In the systems with d-elements, sp 3 -hybridized structures of MnC 2 O 5 , [12] FeFeC 3 O 12 , and FeFeC 4 O 13 [13] were synthesized. Systems with p-elements have not yet been investigated, and in the present work, we investigate such a system, namely PbOÀ CO 2 .…”
Section: Introductionmentioning
confidence: 99%